PENGGUNAAN GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI ERA DIGITAL PADA SISWA SD NEGERI DI KECAMATAN MEGAMENDUNG BOGOR - Nur Hadi; Hendro Prasetyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The objective of this research was to conduct an in-depth analysis of the effect of implementing a gamification-based learning model on the learning motivation level of primary school students in the current digital era. The main findings of this study stem from the increasing trend of digital technology use in the learning process, which necessitates innovative teaching strategies to effectively enhance active student participation. The research method used was a quantitative method with a quasi-experimental design, employing a pretest-posttest comparison. The research sample consisted of approximately 50 fifth-grade students from SD Negeri Sukamaju and SD Negeri Sukamahi 01, located in the Megamendung Sub-district, Bogor Regency.The data collection tool used in this study was a learning motivation questionnaire presented in the form of a Likert scale with a score range of 1 to 5, consisting of 20 statements that had undergone validity and reliability testing to ensure accuracy and consistency of the measurement results. The data obtained were then analyzed using a paired sample t-test to determine the difference in students' learning motivation scores before and after the treatment was given. The results of the statistical analysis showed a significant difference between students' learning motivation scores before and after the implementation of gamification-based learning, with a value of $t(49) = 7.25$ and $p < 0.05$. This clearly indicates that the use of game elements in learning activities can increase student motivation and engagement. Thus, it can be concluded that gamification is an effective learning strategy for maximizing student learning motivation in a traditional classroom environment in the digital era.The implications of this research affirm the importance for educators to integrate game elements such as levels, challenges, and points into the learning process, in order to create an engaging, interactive, and enjoyable learning experience for students.